'Son of Arabia, son of Nazareth, and my son': Herut's stand on the imposition of the Military Government 1948-1966. Issue 4 (4th July 2022) - Mark, Maya
Abstract: This article focuses on the campaign waged by Herut, a right-wing National-Liberal party and its leader, Menachem Begin, to abolish the Military Government imposed on the Arab citizens of Israel between the years 1948-1966. The article draws on multiple sources that have not yet been studied to analyze Herut's struggle for the annulment of the Military Government, while placing it in a broad historical and political context. It shows that Herut derived certain political benefits by campaigning for the annulment of the Military Government. However, it also establishes that Herut paid a price for its campaign, suffering criticism from within the right-wing political camp and wrestling with allegations from the left-wing political camp. The analysis of Herut's campaign for the annulment of the Military Government illuminates the liberal ideological foundations of the movement that has held sway in Israel for over four decades, affirming its commitment to liberal values, and the belief of its founding father, Begin, in civic equality between Jews and Arabs in Israel.